2023
DOI: 10.3390/ani13030502
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota, Bile Acids, Sterols, and Fatty Acids in Dogs with Chronic Enteropathy Fed a Home-Cooked Diet Supplemented with Coconut Oil

Abstract: Medium-chain fatty acids (MCFAs) are considered to be interesting energy sources for dogs affected by chronic enteropathies (CE). This study analyzed the clinical scores, fecal microbiota, and metabolomes of 18 CE dogs fed a home-cooked diet (HCD) supplemented with virgin coconut oil (VCO), a source of MCFA, at 10% of metabolizable energy (HCD + VCO). The dogs were clinically evaluated with the Canine Chronic Enteropathy Activity Index (CCECAI) before and at the end of study. Fecal samples were collected at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 81 publications
(108 reference statements)
1
5
0
Order By: Relevance
“…Both supplementation with pinitol and protocatechuic acid have been shown to alleviate inflammation and clinical signs in rodent models of ulcerative colitis 86 , 90 . Results are consistent with previous studies, which have found several phytosterols, including campesterol, fucosterol, and stigmasterol to be altered in fecal samples of dogs and cats with CE 24 , 82 , 91 .…”
Section: Discussionsupporting
confidence: 92%
“…Both supplementation with pinitol and protocatechuic acid have been shown to alleviate inflammation and clinical signs in rodent models of ulcerative colitis 86 , 90 . Results are consistent with previous studies, which have found several phytosterols, including campesterol, fucosterol, and stigmasterol to be altered in fecal samples of dogs and cats with CE 24 , 82 , 91 .…”
Section: Discussionsupporting
confidence: 92%
“…Studies in healthy dogs have characterized the microbial-derived BAs during the development of puppies [ 114 ], as well as the impact of antimicrobials [ 59 , 115 , 116 , 117 , 118 ] and diet [ 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ] on the BA pools of healthy dogs. Additional studies on disease states have largely focused on the context of gastrointestinal [ 52 , 64 , 127 , 128 , 129 , 130 , 131 ] and pancreatic disease [ 128 , 132 ], with additional information characterizing microbial-derived BAs in canine obesity [ 119 , 125 ], diabetes mellitus [ 113 ], and myxomatous mitral valve disease (MMVD) [ 133 ]. The following sections of this review detail the existing veterinary literature describing microbial-derived BAs in dogs.…”
Section: Canine Microbial-derived Bile Acidsmentioning
confidence: 99%
“…Dogs with gastrointestinal diseases, including canine chronic inflammatory enteropathy (CIE) [ 52 , 64 , 127 , 128 , 130 , 131 ], exocrine pancreatic insufficiency (EPI) [ 128 ], and canine non-infectious acute diarrhea [ 129 ], have alterations in BA pools consistent with BA dysmetabolism. Herein, evidence for each disease state will be presented and reviewed.…”
Section: Canine Microbial-derived Bile Acidsmentioning
confidence: 99%
See 2 more Smart Citations